Crime, Fear, and Legitimating Ideologies: State of the Union Addresses as Hegemonic Strategy. (December 2014) - Hawdon, James; Wood, Robert
Beckett and Sasson argue that the wars on crime and drugs of the 1980s and 1990s were part of an elite-engineered hegemonic strategy aimed at replacing the welfare state with the security state. As the welfare state came under attack, a new hegemonic strategy emerged that attacked welfare policies and promoted "tough on crime" policies. Yet, Beckett and Sasson note that for the new hegemonic strategy to be successful, it must be rooted in the experiences and cultural beliefs of the general population. We investigate the possibility of an elite-engineered effort to build support for tough on crime policies by conducting a time series analysis using General Social Survey data and statements by presidents in State of the Union addresses from 1972 to 2010. Specifically, we predict aggregate levels of fear of crime and support for welfare spending with presidential mentions of "crime" and "welfare" in State of the Union addresses. Our results indicate that fear increases when presidents discuss crime and welfare in the State of the Union. In addition, fear of crime is inversely related to supporting welfare spending. These relationships hold even after controlling for crime rates. Our findings offer support for Beckett and Sasson's argument.